Every city shall be forsaken : urbanism and prophecy in ancient Israel and the Near East - Grabbe, Lester L.; Haak, Robert D. (Robert Donel), 1949- (Journal for the study of the Old Testament. Supplement series ;, 2001)
Urbanism in ancient society has now become an important topic for both classical and ancient Near Eastern scholars. Equally, the question of prophecy as social institution and literary corpus has been increasingly problematized. The essays in this volume bring together these crucial aspects of modern biblical research, the scope ranging from methodological issues about sociology and urbanism to Assyrian prophecies and specific biblical texts. An introductory chapter surveys recent anthropological study on urbanism, summarizes the essays, and places the different contributions in context.